Mechanical strength of stainless steel and titanium alloy mini-implants with different diameters: an experimental laboratory study - Sérgio Estelita Barros; Viviane Vanz; Kelly Chiqueto; Guilherme Janson; Eduardo Ferreira (SpringerOpen, 2021)
Abstract Background The mechanical strength of mini-implants is a critical factor due to their small diameters. Currently, it is not possible to state whether there is a relevant difference between the mechanical properties of stainless steel (SS-MIs) and titanium alloy mini-implants (TA-MIs). The objective of this study was to test the null hypothesis that there is no difference in the mechanical strength of SS-MIs and TA-MIs, and to analyze, by scanning electron microscopy (SEM), the SS-MI, and TA-MI threads resistance to morphological damage after insertion. Methods A standardized sample of 504 SS-MIs and TA-MIs with diameters ranging from 1.2 mm to 1.8 mm was used. Torsional fracture was performed in 154 MIs. Flexural strength of 280 MIs was evaluated at 1 mm and 2 mm-deflection. The threads of 70 MIs were morphologically analyzed by scanning electron microscopy (SEM), before and after their insertion in high-density artificial bone blocks. Comparisons between SS-MIs and TA-MIs were performed with t tests or Mann-Whitney U tests. A multiple linear regression analysis was used to evaluate the influence of variables on the ranging of MI mechanical strength. Results SS-MIs had higher fracture torque. The mean difference between the SS-MIs and TA-MIs fracture torque was of 4.09 Ncm. The MI diameter explained 90.3% of the total variation in fracture torque, while only 2.2% was explained by the metallic alloy. The SS-MI group presented a higher deformation force during the 1mm and 2mm-deflection. The mean difference between the flexural strength of SS and TA-MIs at 1 mm and 2 mm-deflection was of 18.21 N and 17.55 N, respectively. There was no noticeable morphological damage to the threads of SS-MIs and TA-MIs. Conclusions The null hypothesis was rejected. SS-MIs were 13.2% and 20.2% more resistant to torsional fracture and deflection, respectively. The threads of the SS-MIs and TA-MIs were not damaged during the insertion and removal process. Thus, the use of SS-MI can reduce the fracture risk without increasing the MI diameter.